Renegades, Pan Groove Out Front - Unknown (Daily Express)
Amoco Renegades and Phase II Pan Groove have taken the lead in the North zone of the Panorama preliminaries. In the East zone, American Stores Exodus and Solo Harmonites are leading. In the South/Central zone, it is Vat 19 Fonclaire and Silver Harps while Pan Round the Neck leaders are Scrunters Pan Grove and Trinidad Nostalgic. A list of the other steelbands that have made it into the semi-finals are mentioned.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Competitions -- Trinidad and Tobago